Towards Managing Educational Institutions for Excellence and Perfection: Reflections - Mosha, Herme J. (Papers in Education and Development, 2018)
Managing educational institutions for excellence and perfection is an article that attempts to draw on good practices in well-performing private denominational schools to illustrate how quality secondary education can be realised in the rest of the system. This follows a national outcry that the quality of secondary education is declining, as demonstrated by poor results in the Certificate of Secondary Education examination. In order to remedy the situation, the writer advocates the need for managers and stakeholders to re-examine the vision, mission and goals of secondary education so that can discern what initiatives need to be institutionalised in order to attain high quality education, excellence and perfection, thereafter to critically review the curriculum package to uncover the needs and expectations, build into the system the requisite capacity to ensure it is effectively being implemented, while constantly seeking feedback, especially from past students and other stakeholders, followed by corrective action.